Theoretical and experimental analysis of precast slabs composed of pre-stressed joists (2022)
The composite precast slabs are composite systems, in which they are constituted by concrete joists (reinforced or prestressed), filling components and a solidarization layer in reinforced concrete. It is a construction system widely used in the world, mainly in Ibero-American countries, such as Brazil and Spain, for example. However, there is still a lack of knowledge about the compatibility between the theoretical results and the experimental ones, since they are composite systems, and the variables can be decisive in the theoretical models. Therefore, this study aimed to compare the theoretical and experimental results of precast composite slabs. This study developed an experimental program of flexing tests for a slab with pre-stressed center joist reinforced on each side with half-longitudinal slab components and a 5 cm mesh-reinforced concrete cover. Experimental variables were the diameter of steel reinforcement and filler material (ceramic blocks or Expanded Polystyrene – EPS blocks). This study has 4 steps: materials characterization, mechanical tests of the joist, effect of filler material in the structural behavior and theoretical and experimental system behavior at fissuring and rupturing. Prestressed joists ruptured in compression regions during bending tests regardless of the diameter of steel reinforcement due to concrete low strength. Filler material did not alter the slabs rupturing load, but EPS blocks allowed considerable deflections. Regarding maximum bending moment, the selected theoretical models had an agreement of up to 99% on experimental values for 4 mm diameter steel-reinforced joists. However, for the joints with 5 and 6 mm wires, the analysis did not prove to be so valid, reaching a ratio of approximately 70 and 60%, respectively.